Comparison of Presidential Term Regulations in Several Countries with Presidential Systems: Indonesia, United States, and Philippines - Ranarosyidah Rihadatul'Asy; Widy Anastasya Putri; Nor Lailatul Mutfaidah (Journal of Indonesian Constitutional Law, 2024)
In the presidential system of government, the Head of Government is held by the President, and the constitution of each country determines his terms of office in the proposal. This research compares presidential term arrangements in Indonesia, the United States, and the Philippines, focusing on the duration of the term of office and period limits. The legal research method used in this research is normative juridical research to answer the issues to be discussed. This research aims to examine three countries with the same system of government but different presidential term periods. The results of this study show that in Indonesia, the president serves for five years with a maximum of two terms. In the United States, the president also has a four-year term limited to two terms. Meanwhile, in the Philippines, the president serves a six-year term without the possibility of re-election. The research found that these different arrangements reflect each country's historical and political context and have implications for political stability, policy continuity, and electoral dynamics.